Copper-Catalyzed C2- or C3-Thioglycosylation of Indoles with N‑(Thioglycosides)succinimides: An Effective Strategy for the Total Synthesis of Isatindigotindolosides - Huang, Jie; Sun, Wen-Wu; Li, Jin-Quan; Ma, Ao-Di; Liu, Ji-Kai; Wu, Bin (Organic letters, 2023)
Isatindigotindolosides, indoles containing a 1-S-β-glucopyranosyl unit at position C2, show promising bioactivity. Here, we report a copper-catalyzed C2- or C3-thioglycosylation of indoles with N-(thioglycosides)succinimides to construct indole alkaloid glucosides. This reaction is widely tolerant of functional groups, as various indoles and thioglycosides are suitable. It also provides a reliable method for performing late-stage modifications of natural products, such as gramine and melatonin. Total syntheses of isatindigotindolosides I and II were successfully accomplished using the C2-thioglycosylation reaction as a key step.